Phenolic compound hydrodeoxygenation nickel phosphide catalyst and preparation method thereof

By using Ce modified Ni2P active phase and composite protective layer in the hydrodeoxygenation catalyst of phenolic compound, the problem of insufficient water tolerance of the catalyst under high temperature and high pressure is solved, achieving a win-win situation of activity and stability, and reducing the Preparation cost.

CN119114127APending Publication Date: 2024-12-13NORTHEAST GASOLINEEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410939882.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing hydrodeoxygenation catalysts have insufficient tolerance to water under high temperature and high pressure conditions, resulting in poor stability and difficulty in achieving a win-win situation of activity and stability, especially in the process of hydrodeoxygenation of phenolic compounds.

Method used

The phenolic compound hydrodeoxyphosphide catalyst is used to form a metal oxide support, Ce-modified Ni2P active phase, and a metal phosphorus oxide and NC composite protective layer embedded in the nitrogen carbon layer, and the nickel hydrodeoxyphosphide catalyst is used to poly cerium citrate and shell The synergistic effect of sugar forms a uniform and firm protective layer, improving the stability and activity of the catalyst.

Benefits of technology

It significantly improves the stability and activity of the catalyst, enhances the tolerance to water, extends the service life of the catalyst, and reduces the preparation cost, achieving efficient hydrodeoxygenation reaction under high temperature and high pressure conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114127A_ABST
    Figure CN119114127A_ABST
Patent Text Reader

Abstract

The invention relates to a phenolic compound hydrodeoxygenation nickel phosphide catalyst. The catalyst is composed of a metal oxide carrier, a Ce-modified Ni2P active phase and a metal phosphorus oxide and NC composite protective layer embedded into a nitrogen-carbon layer. The invention also relates to a preparation method of the phenolic compound hydrodeoxygenation nickel phosphide catalyst and a method for catalytically preparing cycloalkane. Starting from optimization of an active phase electronic structure of the catalyst and regulation and control of surface properties, a composite catalyst composed of a chitosan-treated metal oxide carrier MxOy, a cerium citrate-modified Ni2P active phase (Ce-Ni2P) and a protective layer obtained through surface treatment is designed; the activity and the stability of the catalyst are improved at the same time through the regulation and control synergistic effect of electronic structures and surface properties of the cerium citrate, the chitosan and the metal phosphorus oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis and relates to a nickel phosphide catalyst for hydrogenation deoxidation of phenolic compounds and a preparation method thereof. Background Art

[0002] As a renewable resource, biomass has attracted much attention due to its high yield, low cost and zero CO2 emission. Biomass mainly includes cellulose, hemicellulose and lignin. Lignin is the second largest biomass resource in nature after cellulose, and it is also the only clean non-petroleum resource in nature that can provide renewable aromatic compounds. The biomass oil obtained by pyrolysis of lignin contains a large number of benzene ring structural units. It is a cheap and clean resource that can be converted into high-energy aromatics and cycloalkanes, and is one of the most promising petroleum supplementary energy sources. However, the biomass oil obtained by pyrolysis has a high oxygen content and contains oxygen-containing compounds such as phenols, ketones, aldehydes, furans, alcohols, ethers and esters, which leads to its low combustion calorific value (≈20 MJ / kg), poor stability and oil solubility, and strong corrosiveness, which greatly limits its practical application. Therefore, it is of great significance to improve the quality of crude biomass oil to achieve its high-grade utilization.

[0003] Hydrodeoxygenation (HDO) is an effective way to convert oxygenated derivatives in inferior crude biomass oil into clean oxygen-free cycloalkanes. Phenolic compounds are typical biomass oil pyrolysis compounds, and there are two main ways to hydrodeoxygenate them: (1) direct deoxygenation (DDO), the deoxygenation products are aromatics; (2) hydrodeoxygenation (HYD), the deoxygenation products are cycloalkanes. Among them, the cycloalkanes obtained by the HYD reaction pathway have high calorific value and low freezing point. They are not only an important component of transportation fuels such as gasoline, diesel and aviation kerosene, but also an important chemical raw material with high product added value. Among the existing hydrodeoxygenation catalysts, precious metal catalysts have high HDO activity, but the catalyst stability is poor and the cost is high. Therefore, the preparation of cheap and highly active non-precious metal HDO catalysts has attracted widespread attention.

[0004] At present, there are many articles and patents reporting the method of using non-precious metal catalysts for preparing hydrocarbon fuels from biomass oil HDO. Among many transition metal catalysts, nickel phosphide (Ni2P) catalyst has become a hot spot in the research field of new HDO catalysts due to its unique metallic properties, semiconductor properties and excellent catalytic performance. However, it is worth noting that since biomass oil HDO is carried out under high temperature and high pressure conditions, the water molecules contained in the raw materials adhere to the surface of the catalyst active phase, affecting the stability of the catalyst, thereby shortening the life of the catalyst and limiting its industrial application. To improve the tolerance of the catalyst to water contained in the raw materials, it is possible to start from the preparation of the catalyst active phase and the carrier. In order to reduce the influence of water contained in the raw materials on the stability of the catalyst under high temperature and high pressure conditions, the invention patent CN1049231968 discloses "a method for preparing a core-shell structure carrier for preparing a hydrodesulfurization catalyst", and the Al2O3@TiO2 core-shell structure carrier synthesized by TiO2-coated Al2O3 improves the activity and thermal stability of the Ni2P catalyst. However, the preparation process of the core-shell structure carrier is relatively complicated, the cost is high, the energy consumption is large, and the degree of stability improvement is limited. Designing a protective layer for the catalyst is an effective strategy to improve its stability, but how to achieve uniform thickness and firmness of the protective layer is the key. Due to the uneven thickness of the protective layer, local corrosion will occur, affecting the stability of the catalyst; if the protective layer is not firmly bonded to the catalyst, it will easily fall off and lose its protective effect on the catalyst. In addition, improving stability often reduces activity to a certain extent. Therefore, based on the characteristics of HDO, it is particularly important to improve the activity of the catalyst while improving the tolerance to water contained in the raw materials through simple and low-cost methods to achieve a win-win situation of catalyst activity and stability, but this "dual-function" protective layer design is rarely reported. In addition, the development of a simple and low-cost preparation method that can form a protective layer with uniform thickness and firm bonding on the catalyst surface has important practical application prospects.

[0005] As the most abundant and typical rare earth element, Ce is particularly attractive due to its rich redox ability, good electronic / ionic conductivity and high affinity for oxygen donors. As a rare earth metal with unique 4f electrons, Ce can significantly improve the catalytic efficiency. However, no relevant research has been reported on the improvement of HDO activity and stability of supported phosphide catalysts by doping Ce in phosphides. Summary of the invention

[0006] The first purpose of the present invention is to provide a nickel phosphide catalyst for the hydrodeoxidation of phenolic compounds, which overcomes the problem that the current catalysts cannot achieve a win-win situation in terms of activity and stability.

[0007] The second object of the present invention is to provide a method for preparing the above-mentioned nickel phosphide catalyst for hydrodeoxidation of phenolic compounds.

[0008] The third object of the present invention is to provide a method for preparing cycloalkanes using the above catalyst.

[0009] The present invention is achieved through the following technical solutions: 1. A nickel phosphide catalyst for the hydrodeoxidation of phenolic compounds, which comprises a metal oxide carrier, a Ce-modified Ni2P active phase, and a composite protective layer of metal phosphorus oxide and NC embedded in a nitrogen-carbon layer.

[0010] 2. According to the above-mentioned method for preparing the nickel phosphide catalyst for hydrodeoxidation of phenolic compounds, the method comprises the following steps: (1) Add 0.05-0.2 g chitosan to 30 mL deionized water and mix well, then add 0.5 g oxide carrier M x O y After stirring for 10 min, the mixture was placed for 10 h, filtered, and the obtained solid was dried at 60 °C for 12 h. The chitosan-treated carrier was recorded as M x O y @Chitosan; (2) Dissolve the Ce source and Ni source in deionized water, place in a magnetic stirrer and stir for 30 min, then add M x O y @Chitosan carrier was stirred for 30 min, Ni loading was 10-30 wt%, Ce loading was 0.5-10 wt%, the molar ratio of Ni to deionized water was 0.001-0.002:1, the mixed suspension was transferred to a polytetrafluoroethylene-lined stainless steel reactor, and hydrothermal reaction was carried out at 120-160 ° C for 6-12 hours. After cooling to room temperature, it was washed alternately with ethanol and deionized water for 3 times, and dried to obtain Ce and chitosan-modified Ce-Ni / M x O y @Chitosan catalyst precursor; (3) The catalyst precursor and phosphorus source were placed in two quartz boats respectively, with the molar ratio of P source to Ni source being 3-6:1. After being placed in a tube furnace, they were phosphated at 420 °C in an inert gas atmosphere for 2 h at a heating rate of 3 °C∙min. -1 After the temperature of the tube furnace is lowered to 50-100°C, the air valve is opened and the oxygen content in the inert gas is adjusted to 0.5-10 v%, and the treatment time is 1-2 hours. The temperature is lowered to room temperature to obtain Ce-Ni2P@PT / M x O y The catalyst, PT, is a composite protective layer of metal phosphorus oxide and NC embedded in the nitrogen-carbon layer on the catalyst surface.

[0011] Furthermore, the M x O y It is a SiO2 or TiO2 carrier.

[0012] Furthermore, the Ni source is any one of nickel chloride, nickel nitrate and nickel acetate.

[0013] Furthermore, the Ce source is cerium citrate.

[0014] Furthermore, the P source is any one of ammonium hypophosphite and sodium hypophosphite.

[0015] Furthermore, the inert gas is N2 or Ar gas.

[0016] 3. According to the above-mentioned method for preparing cycloalkanes by catalytic hydrodeoxidation of phenolic compounds using nickel phosphide catalyst, decalin is used as solvent, phenolic compounds are used as raw materials, the mass percentage of phenolic compounds in the reaction system is 2-5%, Ce-Ni2P@PT / M x O y The mass ratio of the catalyst to the phenolic compound is 0.002-0.008:1, the reaction temperature is 200-275°C, the hydrogen partial pressure is 2-4 MPa, the reaction time is 0.5-2 hours, and the reaction is stopped to obtain the product.

[0017] Furthermore, the phenolic compound is one of phenol, o-cresol, m-cresol and p-cresol.

[0018] The positive effect of adopting the above technical solution: The present invention designs a chitosan-treated metal oxide carrier M based on the optimization of the electronic structure of the catalyst active phase and the regulation of surface properties. x O y The composite catalyst is composed of Ni2P active phase modified by cerium citrate (Ce-Ni2P) and metal phosphorus oxide, which improves the activity and stability of the catalyst at the same time through the synergistic effect of the electronic structure and surface properties of cerium citrate, chitosan and metal phosphorus oxide; (1) The catalyst of the present invention uses cheap Ni2P as the active phase and adopts a one-pot method to prepare Ce and chitosan-modified Ce-Ni / M x O y @Chitosan catalyst precursor, and then through a step of pyrolysis and surface treatment, Ce-Ni2P@PT / M x O y Catalyst; The catalyst preparation process does not use organic solvents or expensive reagents, does not require complex processes or expensive equipment, and has the advantages of simple preparation process and low cost; (2) Ce-Ni2P@PT / M x O yThe main reasons for the excellent stability of the catalyst are: (a) Using cerium citrate as the cerium source, during the phosphating process, the citrate ions and chitosan decompose to form a NC protective layer on the catalyst surface, and then after air surface treatment, a Ce-Ni layer embedded in the nitrogen-carbon layer is formed. x P y O z PT composite protective layer formed with NC. The in-situ grown protective layer is firmly bonded to the catalyst and is not easy to fall off. (b) The PT protective layer improves the hydrophobicity of the catalyst surface and inhibits the H2O molecules contained in the raw materials from adhering to the catalyst surface, thereby reducing the probability of the catalyst reacting with H2O under high temperature and high pressure, and can significantly improve the stability of the catalyst; (c) The synergistic effect of the doped Ce and the PT protective layer effectively improves the structural stability of the catalyst itself, thereby improving its stability during the HDO reaction; (3) The method provided by the present invention for improving the activity and stability of nickel phosphide catalyst for hydrodeoxidation of phenolic compounds improves HDO activity and cycloalkane selectivity mainly because: (a) the surface of the oxide carrier treated with chitosan contains abundant hydrophilic groups such as amide, hydroxyl and carboxyl groups, which makes the oxide carrier more uniformly dispersed in the aqueous solution, and controls the loading sites of Ni through surface groups, inhibits the aggregation of Ni, improves the binding force and dispersibility of Ni and the carrier, and helps to obtain a highly dispersed Ni2P catalyst, thereby improving its HDO activity; (b) using cerium citrate as a Ce source can regulate the electronic structure of the Ni2P catalyst and improve its HDO activity; (c) using cerium citrate as a Ce source, during the phosphating process, citric acid and chitosan decompose to produce a large amount of gas, which can regulate the catalyst pore structure and increase the specific surface area of ​​the catalyst. The pore structure regulation is conducive to the full utilization of the active sites inside the catalyst, and the large specific surface area is conducive to the high dispersion of the active phase, thereby improving the activity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The preparation process of the catalyst; Figure 2 XRD pattern of Ce-Ni2P@PT / SiO2 catalyst; Figure 3 TEM of Ce-Ni2P@PT / SiO2 catalyst; Figure 4 The molecular structure diagram of chitosan; Figure 5 is the Ni in aqueous solution x O y @Schematic diagram of loading on chitosan carrier; Figure 6 The effect of water on the stability of Ce-Ni2P@PT / SiO2 catalyst; Figure 7 The formation mechanism of the composite protective layer PT of Ce-Ni2P@PT / SiO2 catalyst; Figure 8 The stability of Ce-Ni2P@PT / SiO2 catalyst during cyclic use. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described below in conjunction with specific embodiments, but it should not be construed as limiting the present invention: Example 1

[0021] This example illustrates the preparation and XRD characterization of Ce-Ni2P@PT / SiO2 catalyst.

[0022] (1) 0.05 g of chitosan was added to 30 mL of deionized water and mixed well. Then 0.5 g of oxide carrier SiO2 was added, stirred for 10 min, and allowed to stand for 10 h. After filtration, the obtained solid was dried at 60 °C for 12 h. The chitosan-treated carrier was recorded as SiO2@chitosan.

[0023] (2) After dissolving cerium citrate and nickel nitrate in deionized water, the mixture was stirred for 30 min on a magnetic stirrer. Then, SiO2@chitosan carrier was added and stirred for 30 min (Ce loading was 0.5 wt%, Ni loading was 20 wt%, and the molar ratio of Ni to deionized water was 0.001:1). The mixed suspension was transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reaction temperature was set at 120 °C and the hydrothermal reaction was carried out for 12 h. After cooling to room temperature, the mixture was washed alternately with ethanol and deionized water for 3 times. After drying, Ce-Ni / SiO2@chitosan catalyst precursor modified with Ce and chitosan was obtained.

[0024] (3) The catalyst precursor and sodium hypophosphite were placed in two quartz boats respectively, with the molar ratio of sodium hypophosphite to nickel nitrate being 3:1. After being placed in a tube furnace, they were phosphated at 420 °C in N2 gas for 2 hours at a heating rate of 3 °C∙min -1 After the temperature of the tube furnace was lowered to 50 °C, the air valve was opened, and the oxygen content in the N2 gas was adjusted to 5v%. After 1 hour of treatment, the temperature was lowered to room temperature to obtain the Ce-Ni2P@PT / SiO2 catalyst. PT represents the Ce-Ni embedded in the nitrogen-carbon layer on the catalyst surface. x P y O z The composite protective layer composed of NC, the preparation process is shown in Figure 1 The preparation process is simple and does not use expensive reagents, and does not require complicated processes or expensive equipment, which greatly reduces the cost of the catalyst.

[0025] In order to compare the effect of Ce, Ni2P@PT / SiO2 catalyst was prepared at the same time. Its preparation method was the same as that of Ce-Ni2P@PT / SiO2 catalyst, except that no Ce source was added.

[0026] In order to compare the effect of chitosan, Ce-Ni2P / SiO2-without chitosan catalyst was prepared at the same time. Its preparation method was the same as that of Ce-Ni2P@PT / SiO2 catalyst, except that chitosan was not added.

[0027] XRD characterization of Ce-Ni2P@PT / / SiO2 catalyst obtained in this example: The obtained Ce-Ni2P@PT / SiO2 catalyst was characterized by XRD and the active phase in the catalyst was analyzed and tested. The results showed that (see Figure 2 ), an amorphous characteristic peak appears near 2θ=23°, which belongs to the characteristic peak of SiO2. The characteristic peaks at 2θ=40.8°, 44.6°, 47.3° and 54.2° are attributed to the Ni2P phase, which are Ni2P(111), (201), (210) and (300) crystal planes (PDF#03-0953), indicating that the active phase in Ce-Ni2P@PT / SiO2 catalyst exists in the form of Ni2P nanoparticles. No diffraction peaks of other Ni phases are seen in the spectrum, indicating that there are only single Ni2P nanoparticles in the catalyst without other impurities.

[0028] Compared with Ni2P@PT / SiO2, no new diffraction peaks appeared in the XRD spectrum of Ce-Ni2P@PT / SiO2 catalyst, but after Ce doping, the peak of (111) crystal plane moved to the high angle side. This shift can be attributed to the interaction with Ni 2+ / Ni 3+ (72 / 62pm) compared to Ce 3 + / Ce 4+ The ionic radius of (103.4 / 92pm) is larger. Heteroatoms with different radii and electronegativity are incorporated into the main body, often replacing the main atoms in the lattice, resulting in local deformation of the atomic arrangement, and showing peak shift in the XRD spectrum, which indicates that Ce is successfully doped into the Ni2P structure, with a strong and stable combination.

[0029] Compared with Ce-Ni2P@SiO2-without chitosan catalyst, no new diffraction peaks appeared in the XRD spectra of Ni2P@PT / SiO2 and Ce-Ni2P@PT / SiO2 catalysts, but the diffraction peak of Ni2P was significantly broadened, indicating that the treatment of the carrier with chitosan can significantly improve the dispersion of Ni2P phase and reduce its grain size. This will help improve the HDO activity of the catalyst. Example 2

[0030] This example illustrates the preparation and TEM characterization of Ce-Ni2P@PT / SiO2 catalyst.

[0031] (1) 0.2 g of chitosan was added to 30 mL of deionized water and mixed well. Then 0.5 g of oxide carrier SiO2 was added, stirred for 10 min, and allowed to stand for 10 h. After filtration, the obtained solid was dried at 60 °C for 12 h. The chitosan-treated carrier was recorded as SiO2@chitosan.

[0032] (2) After dissolving cerium citrate and nickel chloride in deionized water, the mixture was stirred for 30 min on a magnetic stirrer. Then, SiO2@chitosan carrier was added and stirred for 30 min (Ce loading was 1.0 wt%, Ni loading was 10 wt%, and the molar ratio of Ni to deionized water was 0.002:1). The mixed suspension was transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reaction temperature was set at 140 °C and the hydrothermal reaction was carried out for 10 h. After cooling to room temperature, the mixture was washed alternately with ethanol and deionized water for 3 times. After drying, Ce-Ni / SiO2@chitosan catalyst precursor modified with Ce and chitosan was obtained.

[0033] (3) The catalyst precursor and sodium hypophosphite were placed in two quartz boats respectively, with the molar ratio of sodium hypophosphite to nickel chloride being 6:1. After being placed in a tube furnace, they were phosphated at 420 °C in Ar gas for 2 h at a heating rate of 3 °C∙min -1 After the temperature of the tube furnace was lowered to 100 °C, the air valve was opened, and the oxygen content in the Ar gas was adjusted to 10 v%. After 2 h of treatment, the temperature was lowered to room temperature to obtain the Ce-Ni2P@PT / SiO2 catalyst, where PT is a composite protective layer of metal phosphorus oxide and NC embedded in the nitrogen-carbon layer on the catalyst surface.

[0034] TEM characterization of Ce-Ni2P@PT / / SiO2 catalyst obtained in this example: The obtained Ce-Ni2P@PT / SiO2 catalyst was characterized by TEM. Figure 3 .Depend on Figure 3 (a) It can be seen that the Ni2P nanoparticles on the catalyst are well dispersed, with a diameter of about 4 to 8 nm, and no agglomeration occurs. This is mainly due to the use of chitosan containing nitrogen and carbon ( Figure 4 ) Treating SiO2, the surface of the carrier contains abundant hydrophilic groups such as amide, hydroxyl and carboxyl, which makes the oxide carrier more evenly dispersed in the aqueous solution, and controls the loading site of Ni through the surface group, inhibiting the aggregation of Ni ( Figure 5 ), improve the binding force and dispersibility of Ni and the carrier, and help to obtain highly dispersed Ni2P catalyst. Figure 3(b) It can also be seen that the stripe spacing exposed in the TEM image is about 0.22 nm, which belongs to the (111) lattice plane of Ni2P, and the PT protective layer composed of metal phosphorus oxide and NC embedded in the nitrogen-carbon layer on the catalyst surface can be clearly seen, and its thickness is about 3.0 nm. This is mainly because after SiO2 is treated with chitosan containing nitrogen and carbon, the N and C elements on the surface of the carrier are rich, and after high-temperature phosphating and surface treatment, a uniform and firm Ce-Ni layer is formed on the catalyst surface. x P y O z This will help improve the stability of the catalyst due to the composite protective layer formed with NC. Example 3

[0035] This example illustrates the preparation of Ce-Ni2P@PT / TiO2 catalyst and the effect of using cerium citrate as a cerium source on the HDO activity of the catalyst.

[0036] (1) 0.1 g chitosan was added to 30 mL deionized water and mixed well. Then 0.5 g oxide carrier TiO2 was added, stirred for 10 min, and allowed to stand for 10 h. After filtration, the obtained solid was dried at 60 °C for 12 h. The chitosan-treated carrier was recorded as TiO2@chitosan.

[0037] (2) After dissolving cerium citrate and nickel chloride in deionized water, the mixture was stirred for 30 min on a magnetic stirrer. Then, the TiO2@chitosan carrier was added and stirred for 30 min (Ce loading was 2.0 wt%, Ni loading was 20 wt%, and the molar ratio of Ni to deionized water was 0.0015:1). The mixed suspension was transferred to a polytetrafluoroethylene-lined stainless steel reactor and the reaction temperature was set to 160 °C. The hydrothermal reaction was carried out for 6 h. After cooling to room temperature, the mixture was washed alternately with ethanol and deionized water for 3 times. After drying, the Ce-Ni / TiO2@chitosan catalyst precursor modified with Ce and chitosan was obtained.

[0038] (3) The catalyst precursor and sodium hypophosphite were placed in two quartz boats respectively, with the molar ratio of sodium hypophosphite to nickel chloride being 4:1. After being placed in a tube furnace, they were phosphated at 420 °C in N2 gas for 2 hours at a heating rate of 3 °C∙min -1 After the temperature of the tube furnace was lowered to 50 °C, the air valve was opened, and the oxygen content in the N2 gas was adjusted to 0.5 v%. After 2 h of treatment, the temperature was lowered to room temperature to obtain the Ce-Ni2P@PT / TiO2 catalyst. PT represents the Ce-Ni embedded in the nitrogen-carbon layer. x P y O z Composite protective layer composed of NC.

[0039] For comparison, cerium nitrate was used instead of cerium citrate, and the catalyst was prepared by the same method as Ce-Ni2P@PT / TiO2 in this example, and was recorded as Ce-Ni2P@PT / TiO2-cerium nitrate.

[0040] The Ce-Ni2P@PT / TiO2 catalyst obtained in the example is used for the hydrogenation of p-cresol to prepare methylcyclohexane: The Ce-Ni2P@PT / TiO2 catalyst was used in the experiment of selective hydrogenation of p-cresol to prepare methylcyclohexane. Decalin was used as solvent to prepare a reaction solution system with a mass fraction of 5% p-cresol. Ce-Ni2P@PT / TiO2 catalyst was added, in which the mass ratio of catalyst to p-cresol solution was 0.008:1, the reactor was sealed, nitrogen was checked for leaks, and hydrogen was replaced three times. Hydrogen was introduced, and the reaction was stirred at 275℃ and 2MPa for 2.5 hours, and the reaction was stopped; the reactor was cooled to room temperature, hydrogen was discharged, the reaction mixture was poured out, and the supernatant was taken to analyze the product composition by gas chromatography. The experimental results show that the conversion rate of p-cresol of Ce-Ni2P@PT / TiO2 catalyst is >99.9%, and the selectivity of methylcyclohexane is 99.9%. Under the same conditions, the conversion rate of p-cresol of Ce-Ni2P@PT / TiO2-cerium nitrate catalyst is only 90.4%, and the selectivity of methylcyclohexane is 90.2%, indicating that the effect of using cerium citrate is obvious. This is mainly because cerium citrate is produced during the preparation of the catalyst precursor. During the subsequent high-temperature phosphating process, cerium citrate decomposes and produces a large amount of gas, which regulates the pore structure of the catalyst, increases the specific surface area of ​​the catalyst, and thus increases the HDO activity of the catalyst. Example 4

[0041] This example illustrates the preparation of Ce-Ni2P@PT / TiO2 catalyst and the effect of cerium doping on the HDO activity of the catalyst.

[0042] (1) 0.2 g chitosan was added to 30 mL deionized water and mixed well, then 0.5 g oxide carrier TiO2 was added, stirred for 10 min, and allowed to stand for 10 h. After filtration, the obtained solid was dried at 60 °C for 12 h. The chitosan-treated carrier was recorded as TiO2@chitosan.

[0043] (2) After dissolving cerium citrate and nickel chloride in deionized water, the mixture was stirred for 30 min on a magnetic stirrer. Then, the TiO2@chitosan carrier was added and stirred for 30 min (Ce loading was 5.0 wt%, Ni loading was 30 wt%, and the molar ratio of Ni to deionized water was 0.0018:1). The mixed suspension was transferred to a polytetrafluoroethylene-lined stainless steel reactor and the reaction temperature was set to 120 °C. The hydrothermal reaction was carried out for 24 h. After cooling to room temperature, the mixture was washed alternately with ethanol and deionized water for 3 times. After drying, the Ce-Ni / TiO2@chitosan catalyst precursor modified with Ce and chitosan was obtained.

[0044] (3) The catalyst precursor and sodium hypophosphite were placed in two quartz boats respectively, with the molar ratio of sodium hypophosphite to nickel chloride being 6:1. After being placed in a tube furnace, they were phosphated at 420 °C in N2 gas for 2 hours at a heating rate of 3 °C∙min -1 After the temperature of the tube furnace was lowered to 50 °C, the air valve was opened, and the oxygen content in the N2 gas was adjusted to 5 v%. After 1 h of treatment, the temperature was lowered to room temperature to obtain the Ce-Ni2P@PT / TiO2 catalyst. PT represents the Ce-Ni embedded in the nitrogen-carbon layer. x P y O z Composite protective layer composed of NC.

[0045] For comparison, without adding cerium citrate, a catalyst was prepared by the same method as Ce-Ni2P@PT / TiO2 in this example, and was recorded as Ni2P@PT / TiO2.

[0046] The Ce-Ni2P@PT / TiO2 catalyst obtained in this example is used for the hydrogenation of m-cresol to produce methylcyclohexane: Ce-Ni2P@PT / TiO2 catalyst was used in the experiment of selective hydrogenation of m-cresol to prepare methylcyclohexane. Decalin was used as solvent to prepare a reaction solution system with a mass fraction of m-cresol of 2%. Ce-Ni2P@PT / TiO2 catalyst was added, in which the mass ratio of catalyst to m-cresol solution was 0.008:1, the reactor was sealed, nitrogen was checked for leaks, and hydrogen was replaced three times. Hydrogen was introduced, and the reaction was stirred at 200 and 250℃, 3MPa for 2 hours, and the reaction was stopped; the reactor was cooled to room temperature, hydrogen was discharged, the reaction mixture was poured out, and the supernatant was taken to analyze the product composition by gas chromatography. The experimental results show that when the reaction temperature is 200℃, the conversion rate of m-cresol is 78.4%, and the selectivity of methylcyclohexane is 92.4%. When the reaction temperature is increased to 250℃, the conversion rate of m-cresol of Ce-Ni2P@PT / TiO2 catalyst is >99.9%, and the selectivity of methylcyclohexane is 99.9%. Under the same conditions, when the reaction temperature is 250°C, the m-cresol conversion rate of the Ni2P@PT / TiO2 catalyst is only 88.6%, and the methylcyclohexane selectivity is 87.2%, indicating that the cerium doping of the present invention can significantly improve the HDO activity and methylcyclohexane selectivity. This is mainly because cerium doping can regulate the electronic structure of Ni2P and improve the intrinsic HDO activity of Ni2P; in addition, cerium citrate is decomposed in the subsequent high-temperature phosphating process during the preparation of the catalyst precursor, producing a large amount of gas, regulating the pore structure of the catalyst, and increasing the specific surface area of ​​the catalyst, thereby improving the HDO activity of the catalyst. Example 5

[0047] This example illustrates the preparation of Ce-Ni2P@PT / SiO2 catalyst and the effect of chitosan on the HDO activity of the catalyst.

[0048] (1) 0.2 g of chitosan was added to 30 mL of deionized water and mixed well. Then 0.5 g of oxide carrier SiO2 was added, stirred for 10 min, and allowed to stand for 10 h. After filtration, the obtained solid was dried at 60 °C for 12 h. The chitosan-treated carrier was recorded as TiO2@chitosan.

[0049] (2) After cerium citrate and nickel chloride were dissolved in deionized water, they were placed in a magnetic stirrer and stirred for 30 min. Then, SiO2@chitosan carrier was added and stirred for 30 min (Ce loading was 5.0 wt%, Ni loading was 30 wt%, and the molar ratio of Ni to deionized water was 0.002:1). The mixed suspension was transferred to a polytetrafluoroethylene-lined stainless steel reactor, and the reaction temperature was set to 120 °C. The hydrothermal reaction was carried out for 24 h. After cooling to room temperature, the mixture was washed alternately with ethanol and deionized water for 3 times. After drying, Ce-Ni / SiO2@chitosan catalyst precursor modified with Ce and chitosan was obtained.

[0050] (3) The catalyst precursor and sodium hypophosphite were placed in two quartz boats respectively, with the molar ratio of sodium hypophosphite to nickel chloride being 5:1. After being placed in a tube furnace, they were phosphated at 420 °C in N2 gas for 2 hours at a heating rate of 3 °C∙min -1 After the temperature of the tube furnace was lowered to 50 °C, the air valve was opened, and the oxygen content in the N2 gas was adjusted to 5 v%. After 1 h of treatment, the temperature was lowered to room temperature to obtain the Ce-Ni2P@PT / SiO2 catalyst. PT represents the Ce-Ni embedded in the nitrogen-carbon layer. x P y O z Composite protective layer composed of NC.

[0051] For comparison, a catalyst was prepared by the same method as Ce-Ni2P@PT / SiO2 in this example without adding chitosan, and was recorded as Ce-Ni2P@PT / SiO2-without chitosan.

[0052] The Ce-Ni2P@PT / / SiO2 catalyst obtained in this example is used for the hydrogenation of o-cresol to prepare methylcyclohexane: Ce-Ni2P@PT / TiO2 catalyst was used in the experiment of selective hydrogenation of o-cresol to prepare methylcyclohexane. Decalin was used as solvent to prepare a reaction solution system with a phenol mass fraction of 2%. Ce-Ni2P@PT / TiO2 catalyst was added, wherein the mass ratio of catalyst to o-cresol solution was 0.002:1, the reactor was sealed, nitrogen was tested for leaks, and hydrogen was replaced three times. Hydrogen was introduced, and the reaction was stirred at 275℃ and 4MPa for 1 hour, and the reaction was stopped; the reactor was cooled to room temperature, hydrogen was discharged, the reaction mixture was poured out, and the supernatant was taken to analyze the product composition by gas chromatography. The experimental results show that the o-cresol conversion rate of Ce-Ni2P@PT / TiO2 catalyst is >96.9%, and the selectivity of methylcyclohexane is 99.9%. Under the same conditions, the conversion rate of o-cresol in Ce-Ni2P@PT / SiO2 without chitosan was only 89.9%, and the selectivity of methylcyclohexane was 89.6%, indicating that after the carrier was treated with chitosan, the loading of active components could significantly improve the HDO activity and methylcyclohexane selectivity. This is mainly due to the treatment of SiO2 with nitrogen- and carbon-containing chitosan, and the surface of the carrier contains abundant hydrophilic groups such as amide, hydroxyl and carboxyl groups ( Figure 4 ), so that the oxide carrier is more evenly dispersed in the aqueous solution, and through the surface group, the Ni loading site is controlled, the Ni aggregation is inhibited, the binding force and dispersibility of Ni and the carrier are improved, which helps to obtain a highly dispersed Ni2P catalyst, thereby improving its HDO activity. Example 6

[0053] This example illustrates the preparation of Ce-Ni2P@PT / SiO2 catalyst and its cyclic stability and water resistance.

[0054] (1) 10 g of chitosan was added to 30 mL of deionized water and mixed well. Then, 0.5 g of oxide carrier SiO2 was added, stirred for 10 min, and allowed to stand for 10 h. After filtration, the obtained solid was dried at 60 °C for 12 h. The chitosan-treated carrier was recorded as SiO2@chitosan.

[0055] (2) After cerium citrate and nickel acetate were dissolved in deionized water, they were placed in a magnetic stirrer and stirred for 30 min. Then, SiO2@chitosan carrier was added and stirred for 30 min (Ce loading was 5.0 wt%, Ni loading was 30 wt%, and the molar ratio of Ni to deionized water was 0.0017:1). The mixed suspension was transferred to a polytetrafluoroethylene-lined stainless steel reactor, the reaction temperature was set to 120 °C, and the hydrothermal reaction was carried out for 12 h. After cooling to room temperature, the mixture was washed alternately with ethanol and deionized water for 3 times. After drying, Ce-Ni / SiO2@chitosan catalyst precursor modified with Ce and chitosan was obtained.

[0056] (3) The catalyst precursor and ammonium hypophosphite were placed in two quartz boats respectively. The molar ratio of ammonium hypophosphite to nickel acetate was 3:1. After being placed in a tube furnace, they were phosphated at 420 °C in Ar gas for 2 hours at a heating rate of 3 °C∙min -1 After the temperature of the tube furnace was lowered to 50 °C, the air valve was opened, and the oxygen content in the Ar gas was adjusted to 5 v%. After 1 h of treatment, the temperature was lowered to room temperature to obtain the Ce-Ni2P@PT / SiO2 catalyst. PT represents the Ce-Ni embedded in the nitrogen-carbon layer. x P y O z Composite protective layer composed of NC.

[0057] For comparison, a catalyst was prepared by the same method as Ce-Ni2P@PT / SiO2 in this example without adding cerium citrate, chitosan, or surface treatment, and was recorded as Ni2P / SiO2.

[0058] For comparison, without adding cerium citrate, a catalyst was prepared by the same method as Ce-Ni2P@PT / SiO2 in this example, and was recorded as Ni2P@PT / SiO2.

[0059] For comparison, a catalyst was prepared by the same method as Ce-Ni2P@PT / SiO2 in this example without adding chitosan, and was recorded as Ce-Ni2P@PT / SiO2-without chitosan.

[0060] For comparison, a catalyst was prepared by the same method as Ce-Ni2P@PT / SiO2 in this example without surface treatment, and was recorded as Ce-Ni2P@PT / SiO2-without surface treatment.

[0061] The Ce-Ni2P@PT / SiO2 catalyst obtained in this example was used for the HDO reaction of m-cresol to study the recycling performance of the catalyst. At the same time, different amounts of water were added to the raw materials to investigate the water resistance stability of the catalyst: Ce-Ni2P@PT / SiO2 catalyst was used in the experiment of selective hydrogenation of m-cresol to prepare methylcyclohexane. A reaction solution system with a mass fraction of 2% of m-cresol was prepared with decahydronaphthalene as solvent, and the molar ratio of water to m-cresol was 0-1.25:1. Ce-Ni2P@PT / SiO2 catalyst was added, wherein the mass ratio of catalyst to m-cresol solution was 0.008:1, the reactor was sealed, nitrogen was checked for leaks, and hydrogen was replaced three times, and then hydrogen was introduced. At 250℃ and 3MPa, the reaction was stirred for 2 hours, and the reaction was stopped; the reactor was cooled to room temperature, hydrogen was discharged, the reaction mixture was poured out, and the supernatant was taken to analyze the product composition by gas chromatography.

[0062] The results of water resistance test are shown in Figure 6 The results show that the initial m-cresol conversion rate of the Ni2P / SiO2 reference catalyst prepared without cerium citrate, chitosan, and surface treatment was only 84.5%. When the water content in the raw material was 1:1.25, the m-cresol conversion rate dropped to 65.7%, which was only reduced by 22.2%, indicating that the activity of the catalyst will decrease rapidly when there is water in the raw material. Compared with the Ni2P / SiO2 catalyst, under the same reaction conditions, when the water content in the raw material was 1:1.25, the m-cresol conversion rates of the reference catalyst Ce-Ni2P@PT / SiO2-Ni2P@PT / SiO2 without surface treatment and without cerium source and Ce-Ni2P@PT / SiO2-without chitosan were reduced by 7.3%, 10.6%, and 17.2%, respectively. This result shows that surface treatment, the introduction of cerium source and chitosan can improve the water resistance stability of the catalyst to a certain extent. This is mainly because the surface treatment can form a nickel-phosphorus-oxygen protective layer on the catalyst surface, which can inhibit the attack of water on the active phase of the catalyst to a certain extent; cerium is embedded in the Ni2P structure to form a more stable Ce-Ni2P structure, which improves the stability of the catalyst; chitosan improves the stability by changing the surface properties of the catalyst and regulating the surface hydrophobicity.

[0063] The initial meta-cresol conversion rate of the Ce-Ni2P@PT / SiO2 catalyst of the present invention is >99.9%. When the amount of water added to the raw material is 1:1.25, the meta-cresol conversion rate drops to 98.6%, which is only reduced by 1.4%, indicating that the catalyst has good water resistance. Compared with the Ni2P / SiO2 catalyst, under the same reaction conditions, when the amount of water added to the raw material is 1:1.25, the stability is improved by 14.9 times. This shows that there is a synergistic effect between the surface treatment, the introduction of the cerium source and the chitosan. In particular, during the high-temperature phosphating process of the chitosan on the surface of the carrier, the NC structure formed is combined with the nickel-phosphorus-oxygen obtained by the surface treatment to form a relatively stable composite structure protective layer of metal phosphorus oxide and NC embedded in the nitrogen-carbon layer ( Figure 7 ), thereby effectively inhibiting the adsorption of water molecules on the catalyst surface and the attack on the active phase, thereby improving the catalyst's water resistance under high temperature and high pressure; in addition, the doping of Ce embedded in Ni2P can form a stable Ce-Ni2P structure. The result of the synergistic effect of these effects, namely the protective layer and the stable Ce-Ni2P structure, makes the catalyst not only have extremely strong water resistance and good service life. The following catalyst cycle stability experiment further confirmed this.

[0064] The used catalyst was washed three times with ethanol and water alternately, and then dried at 80 °C for 12 h before reuse. The stability of the catalyst during recycling is shown in Table 1. Figure 8 The catalyst was recycled for 6 times, and the conversion rate of meta-cresol was still >99.9%, and the selectivity activity of cyclohexane was >99.9%, indicating that the catalyst has good recycling stability. The good stability of the catalyst is attributed to the synergistic effect between the PT composite protective layer on the catalyst surface and the Ce embedded in Ni2P to form a stable Ce-Ni2P structure.

[0065] The present invention designs a chitosan-treated metal oxide carrier M based on the optimization of the electronic structure of the catalyst active phase and the regulation of surface properties. x O y The composite catalyst composed of cerium citrate modified Ni2P active phase (Ce-Ni2P) and metal phosphorus oxide improves the activity and stability of the catalyst at the same time through the synergistic effect of the electronic structure and surface properties of cerium citrate, chitosan and metal phosphorus oxide.

Claims

1. A nickel phosphide catalyst for hydrodeoxidation of phenolic compounds, characterized in that: The catalyst consists of a metal oxide support, a Ce-modified Ni2P active phase and a composite protective layer of metal phosphorus oxide and NC embedded in a nitrogen-carbon layer.

2. The method for preparing the nickel phosphide catalyst for hydrodeoxidation of phenolic compounds according to claim 1, characterized in that: The method comprises the following steps: (1) Add 0.05-0.2 g chitosan to 30 mL deionized water and mix well, then add 0.5 g oxide carrier M x O y After stirring for 10 min, the mixture was placed for 10 h, filtered, and the obtained solid was dried at 60 °C for 12 h. The chitosan-treated carrier was recorded as M x O y @Chitosan; (2) Dissolve the Ce source and Ni source in deionized water, place in a magnetic stirrer and stir for 30 min, then add M x O y @Chitosan carrier was stirred for 30 min, Ni loading was 10-30 wt%, Ce loading was 0.5-10 wt%, the molar ratio of Ni to deionized water was 0.001-0.002:1, the mixed suspension was transferred to a polytetrafluoroethylene-lined stainless steel reactor, and hydrothermal reaction was carried out at 120-160 ° C for 6-12 hours. After cooling to room temperature, it was washed alternately with ethanol and deionized water for 3 times, and dried to obtain Ce and chitosan-modified Ce-Ni / M x O y @Chitosan catalyst precursor; (3) The catalyst precursor and phosphorus source were placed in two quartz boats respectively, with the molar ratio of P source to Ni source being 3-6:

1. After being placed in a tube furnace, they were phosphated at 420 °C in an inert gas atmosphere for 2 h at a heating rate of 3 °C∙min. -1 After the temperature of the tube furnace is lowered to 50-100°C, the air valve is opened and the oxygen content in the inert gas is adjusted to 0.5-10 v%, and the treatment time is 1-2 hours. The temperature is lowered to room temperature to obtain Ce-Ni2P@PT / M x O y The catalyst, PT, is a composite protective layer of metal phosphorus oxide and NC embedded in the nitrogen-carbon layer on the catalyst surface.

3. The preparation method according to claim 2, characterized in that: The M x O y It is a SiO2 or TiO2 carrier.

4. The preparation method according to claim 2, characterized in that: The Ni source is any one of nickel chloride, nickel nitrate and nickel acetate.

5. The preparation method according to claim 2, characterized in that: The Ce source is cerium citrate.

6. The preparation method according to claim 2, characterized in that: The P source is any one of ammonium hypophosphite and sodium hypophosphite.

7. The preparation method according to claim 2, characterized in that: The inert gas is N2 or Ar gas.

8. The method for preparing cycloalkanes by catalytic hydrodeoxidation of phenolic compounds using nickel phosphide catalyst according to claim 1, characterized in that: Using decahydronaphthalene as solvent and phenolic compounds as raw materials, the mass percentage of phenolic compounds in the reaction system is 2-5%, Ce-Ni2P@PT / M x O y The mass ratio of the catalyst to the phenolic compound is 0.002-0.008:1, the reaction temperature is 200-275°C, the hydrogen partial pressure is 2-4 MPa, the reaction time is 0.5-2 hours, and the reaction is stopped to obtain the product.

9. The method according to claim 8, characterized in that: The phenolic compound is one of phenol, o-cresol, m-cresol and p-cresol.